Urban bus fleet routing in transportation network equipped with park-and-ride: a case study of Babol, Iran - Khakbaz, Amir; Nookabadi, Ali S.; Boushehri, Seyyed N. S. (Transport, 2017)
Recently, most cities have tried to connect park-and-ride facilities with public transit vehicles. The present study aims to design urban bus routes in the transportation network equipped with park-and-ride. Seven important factors which affect the design of urban bus network are identified through the literature review. These factors include demand coverage, route directness, passengers’ satisfaction, minimum length of bus route, budget, use of existing bus routes and number of lines. In this article, by use of the mentioned factors, a new model is developed to determine the urban bus routes. The new model figures the routes with park-and-ride as origin and Central Business District (CBD) as destination, in such a manner that the covered demand is maximized. Our novel method is more effective than other options currently available. In fact, it uses the most important factors in designing urban bus routes. Furthermore, an efficient Genetic Algorithm (GA) based approach is represented to solve large-scale problems. Numerical results show the effectiveness of this approach. At last, the developed model is applied to design the urban bus routes in the transportation network of Babol (Iran).